Skidding and cage whirling of angular contact ball bearings: Kinematic-hertzian contact-thermal-elasto-hydrodynamic model with thermal expansion and experimental validation. (1st March 2022) - Gao, Shuai; Chatterton, Steven; Pennacchi, Paolo; Han, Qinkai; Chu, Fulei
Graphical abstract: Highlights: Accurate modeling of the skidding phenomenon that occurs in angular contact ball bearings for low axial loads. Introduction of a new model using a kinematic-Hertzian-thermo-elasto-hydro-dynamic model. Experimental validation on data in different operating conditions. Discussion of cage whirling as a consequence of bearing deformations owing to operating conditions. Abstract: The occurrence of skidding and overskidding behaviour is likely to scratch rolling element raceways and lead to a significant temperature rise and thermal deformation. The ball-cage interaction and cage whirling motion are likely to oscillate as this skidding is aggravated. To address the damage problems introduced by skidding behaviour, a kinematic-Hertzian contact thermal-elasto-hydrodynamic (KH-TEHD) model with a 5-layer loop structure is proposed. Various factors are considered in the model, including the dynamic beahviour of bearing components, quasi-static analysis on bearing load distribution and deformation of bearing components, and the miscellaneous forces (unbalanced force, collision tangential friction, drag force) acting on the ball and cage. Ball-raceway lubrication, lubricant temperature rise, thermal expansion of shaft and bearing housings, and hydrodynamic pressure acting between the cage surface and guide-ring surface are established in this paper. A 7307AC bearing experimental study under varying operating speeds, axial loads and two lubricating conditions is conducted to validate the accuracy and effectiveness of the KH-TEHD model. The superiority of the developed model is illustrated by comparison with previous models, and the results suggest that the thermal expansion and cage-guide ring hydrodynamic pressure cannot be ignored. After comparisons with literature results, it is found that the overskidding degree is approximately proportional to the square of the bearing size under the same level of operating speed. The maximum thermal deformation at the bearing raceway under starvation lubrication reaches 4 times the ball-raceway clearance. The cage simulation results indicate that the cage whirling oscillation amplitude increases with increasing operating speed and unbalanced mass and generally decreases with increasing axial load. The proposed model and discussion of the results are useful for mitigating the skidding degree under certain conditions and avoiding cage instability and wear.